Reinforcement of sheep-bone derived hydroxyapatite with bioactive glass - (:unkn) unknown (KOREAN ASSOC CRYSTAL GROWTH, INC, 2017)
Productions, mechanical and microstructural analyses of bioglass/sheep hydroxyapatite (SHA) composites are introduced. Bioglass were added to calcinated SHA with various concentrations 5 and 10 wt. %. Powder mixture compacted with pressure (350 MPa) in steel moulds to obtain cylinder samples. As the next step, samples sintered in air at various temperatures (1000, 1100, 1200, 1300 degrees C for 4 hrs). Compression strength test, density and the Vickers microhardness (HV) measurements were carried out and microstructural characterizations were performed by scanning electron microscopy (SEM) and X-ray diffraction analysis (XRD) in order to determine optimum sintering temperature and mechanical properties. At last average hardness value 1612 +/- 80 HV, average density of 2.65 +/- 0.31 g/cm(3), and compressive strength value of sigma(avr) = 99.14 MPa were obtained by sintering at 1300 degrees C with the addition of 5 wt. % bioglass in SHA. Results show potential of brittle biomaterial but resistant to plastic strain.
Keywords: Composites; Sheep bone; Hydroxyapatite (HA); Bioglass; Bioceramic; MECHANICAL-PROPERTIES; COMPOSITES